HUBUNGAN PERILAKU MEROKOK DENGAN KUALITAS TIDUR PADA MAHASISWA FAKULTAS TEKNIK UPN VETERAN JAKARTA TAHUN 2022 - Aulia Putri Sulaeman (2022)
Cigarettes are a familiar thing among students. Various functions of cigarettes such as stress relief while studying and as a social function. Cigarettes can directly affect the body's natural clock. This is caused by nicotine and other toxic substances contained in it. The purpose of this study was to determine the relationship between smoking behavior and sleep quality in students of the Faculty of Engineering, UPN Veteran Jakarta in 2022. This study used a cross-sectional study design with a proportional stratified random sampling technique. Sampling totaling 100 respondents. Data collection using an online questionnaire GoogleForm platform. The instrument used is the respondent's characteristics questionnaire, for the smoking behavior questionnaire the Glover-Nilsson Smoking Behavioral Questionnaire (GN-SBQ) and sleep quality using the Pittsburgh Sleep Quality Index (PSQI). This study uses univariate and bivariate analysis with Chi-Square test. The results showed that there was a significant relationship between smoking behavior and sleep quality for students of the Faculty of Engineering, UPN Veteran Jakarta in 2022 with p value = 0.003 OR = 13,241 (95% CI: 1,524-115,046). Therefore, it is expected that students can change their lifestyle from factors that allow worsening sleep quality, one of which is smoking behavior by reducing their consumption.